John Lydgate and the making of public culture - Nolan, Maura (Cambridge University, 2013)
Re-interpreting the work of poet John Lydgate in the context of his role in the English literary tradition and literary culture of the late medieval period, Nolan examines the development, shape and nature of the emerging English public culture of the fifteenth century.